A Statistical Power Analysis of the Quantitative Techniques Used in the "Journal of Research in Music Education," 1987 through 1991 - Daniel, Thomas Dyson ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2010)
Statistical power in music education was examined by taking an in-depth look at quantitative articles published in the "Journal of Research in Music Education" between 1987 and 1991, inclusive. Of the 109 articles of the period, 78 were quantitative, with both parametric and nonparametric procedures considered. Sample sizes were those reported by the authors. Effect sizes were estimated according to the guidelines developed by J. Cohen (1988), and his power analysis tables were used. The overall median power for the articles was 0.13 for detecting small effects, 0.64 for detecting medium effects, and 0.97 for detecting large effects. Implications of these findings, limitations of the study, and suggestions for future music-education research are discussed. In general, more attention should be placed on a priori power analyses of research designs. Adequate sample sizes should be chosen and a greater understanding and application of the concept of effect size is needed in music education research. Six tables are included. (Contains 18 references.) (SLD)
ERIC Note: Paper presented at the Annual Meeting of the Mid-South Educational Research Association (New Orleans, LA, November 10-12, 1993).
Microfiche.
Keywords: Effect Size; Estimation (Mathematics); Music Education; Nonparametric Statistics; Power (Statistics); Research Design; Research Methodology; Sample Size; Sampling; Journal of Research in Music Education; A Priori Tests; Information Analyses; Reports, Evaluative; Speeches/Meeting Papers